(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This work aims to estimate the maximum shear capacity of deep beams RC members strengthened by Near-Surface Mounted (NSM) steel bars. This is done by using an assumed semi-empirical formula that depends on experimental tests. This formula will cover many principal parameters such as shear span to effective depth ratios (a/d), orientation angle of NSM steel bars, concrete compressive strength (f′c), bar’s diameter and their spacing. So, thirteen reinforced concrete deep beams with different (a/d) ratios equals (0.85, 1.136 and 1.42) were tested. These beams are categorized into three groups depending on (a/d) ratio, which contained one unstrengthen beam as a control specimen and others strengthened beams by different schemes of NSM steel bars. A comparison between the calculated and experimental values shows good agreement with high coefficient of determination (R2=95.4%). The proposed formula is also used to estimate shear capacity of some specimens that found in some previous literatures to confirm the validity of the formula in estimating shear capacity of different cases. Good agreement with low (COV) of the predicted shear capacity with the experimental values that found in literatures was obtained.